Numerical study of laser-induced cavitation bubble with consideration of chemical reactions - Wang, Chengyan; Yan, Hong; Zhang, Ruifan; Chen, Fuzhen; Liu, Fan (Ultrasonics sonochemistry, 2024)
•Chemical reactions in laser-induced cavitation bubble are considered for the first time by numerical simulations.•The effects of overall reaction and detailed elementary reactions on the cavitation bubble are evaluated, respectively.•The properties of cavitation bubble are compared for two conditions, infinite domain and near-wall. Cavitation generated during injector jetting can significantly affect fuel atomization. Laser-induced cavitation bubble is an important phenomenon in laser induced plasma ignition technology. Limited by the difficulties in experimental measurements, numerical simulations have become an important tool in the study of laser-induced cavitation bubble, but most previous numerical models used to study the dynamics of laser-induced cavitation bubble usually ignore the effect of chemical reactions. In this study, the finite volume method is used to solve the compressible two-dimensional reynolds averaged Navier–Stokes equation by considering the heat and mass transfer as well as the chemical reactions within the cavitation bubble. The effects of overall reaction and elementary reactions on the cavitation bubble are evaluated, respectively. It is found that by additionally considering chemical reactions within the numerical model, lower maximum temperatures and higher maximum pressures are predicted within the bubble. And the generated non-condensable gases produced by the chemical reactions enhance the subsequent expansion process of the cavitation bubble. Besides, the effect of the one-sided wall boundary condition on cavitation bubble is compared with the infinite boundary condition. Influenced by the wall boundary, the cavitation bubble forms a localized high pressure on the side of the bubble away from the wall during the collapse process, which causes the bubble to be compressed into a ”crescent” shape. The maximum pressure and temperature inside the bubble are lower due to localized losses caused by the wall.